A Short Review on Chicken Heterophil - N. Anand Laxmi (Research Aspects in Agriculture and Veterinary Science Vol. 1, 2021)
In birds the major leukocytes involved in phagocytosis function are heterophils. Heterophils are polymorphonuclear leukocytes. They are a part of the innate immune system. When chickens are encountered by pathogens, they generate the primary response. Heterophils are counterparts of neutrophils in mammals, like neutrophils, their response to pathogens is quick, and get activated quickly which is by chemotaxis of heterophils. Detection of Bacteria, their proteins or their structures is through certain specialized receptors present in the immune cells called as Toll Like Receptors (TLR’s). They contain antimicrobial substances which are released when encountered by pathogens. Their functions are genetically controlled. They are highly phagocytic and antimicrobial activity is characterised through various ways.